Associations of urinary phytoestrogens with all-cause and cardiovascular mortality in adults: a population-based cohort study - Xuan, Chao; Zhao, Cong; Zhou, Ting-Ting; Guo, Jun-Jie; Pan, Deng; Wang, Zi-Bo; He, Guo-Wei (Frontiers in Endocrinology, 2024)
The overall understanding of the correlations between mortality risk and phytoestrogens in general population remains limited. We examined the association between urinary phytoestrogen levels and all-cause and cardiovascular mortality based on the National Health and Nutrition Examination Survey (NHANES).Methods: Weighted Cox proportional hazard regression models were employed to calculate adjusted hazard ratios (HRs) and their 95% confidence intervals (CIs). Nonlinear relationships were assessed using multivariable-adjusted restricted cubic splines.In the fully adjusted model, the highest quartiles of urinary genistein levels were correlated with significantly elevated all-cause (HR = 1.36, 95%CI: 1.16-1.59) and cardiovascular (HR = 1.58, 95%CI: 1.20-2.09) mortality. Urinary enterolactone levels in the third quartile were associated with reduced all-cause (HR = 0.77, 95%CI: 0.65-0.90) and cardiovascular (HR = 0.74, 95%CI: 0.55-0.99) mortality. In the highest quartiles of urinary daidzein levels, the cardiovascular mortality was significantly increased (HR = 1.44, 95%CI:1.09-1.90). RCS showed an non-linear relationship between urinary daidzein levels and all-cause mortality (P = 0.04) .In the context of a nationally representative sample, genistein exhibited associations with elevated all-cause and cardiovascular mortality, whereas enterolactone showed an association with reduced mortality. The dose-response relationship between urinary daidzein levels and all-cause mortality as well as sex-specific disparities in the impact of phytoestrogen levels should be considered.